What’s Left of Blackness - Fisher, T. author. aut Link
XIX, 189 p. 2 illus.
Keywords: This book analyzes the political transformations in black women's socially engaged community-based political work in England in the late twentieth century. It situates these shifts alongside Britain's political economy and against the discourse and deployment of blackness as a political imaginary in which to engage in struggles for social justice.